The Marshall Fire: Scientific and policy needs for water system disaster response - Whelton, Andrew J.; Seidel, Chad; Wham, Brad P.; Fischer, Erica C.; Isaacson, Kristofer; Jankowski, Caroline; MacArthur, Nathan; McKenna, Elizabeth; Ley, Christian (AWWA water science, 2023)
The 2021 Marshall Fire was the costliest fire in Colorado's history and destroyed more than 1,000 homes and businesses. The disaster displaced over 40,000 people and damaged six public drinking water systems. A case study was developed to better understand decisions, resources, expertise, and response limitations during and after the wildfire. The fire caused all water systems to lose power. Power loss was sometimes coupled with structure destruction, distribution depressurization, and the failure of backup power systems. These consequences jeopardized fire‐fighting support and allowed for volatile organic compound and semi‐volatile organic compound contamination of water distribution systems. Water system staff, with help from neighboring systems and external technical experts, stabilized the infrastructure, found and removed the contamination, and restored services. Actions were identified for utilities, governments, and researchers that could help communities minimize wildfire impacts, better protect workers and the population, and enable water systems to more rapidly respond and recover.